MITIGASI PENANGGULANGAN TUMPAHAN SLUDGE OIL DI KAWASAN STRATEGIS PARIWISATA KABUPATEN BINTAN - Hendra Kurniawan (LPPM Institut Pendidikan Nusantara Global, 2023)
Environmental pollution is one of the targets in the goals of sustainable development. Bintan Regency as a strategic tourism area and located in the border area and the busiest route in the world, the malacaa strait is one of the areas that is always seen by sludge oil spills. This study aims to analyze the countermeasures that should be carried out by the goverment in tackling sludge oil pollution in the tourism strategic area of Bintan Regency. This research is a descriptive study using a qualitative approach. Data was collected through interwiews, literacy and direct observation. The results of the research show that the prevention efforts in the form of forming a team to deal with sludge oil spills at the sea stil have weaknesses. Because the operational mechanism has not been celarly structured. The knowledge and awareness of the team members is still limited and the budged allocation for the marine oil handling team has not been budgeted centrally. The lack of use of technology in handling pollution has also become a serious problem resulting in incomplete handling of sludge oil.